Falcaria vulgaris L. hydroalcoholic extract protects against harmful effects of mercuric chloride on the rat kidney - Ali Ghanbari; Cyrus Jalili; Amir Abdolmaleki; Mohsen Zhaleh; Armin Zarinkhat; Nasim Akhshi (Avicenna Journal of Phytomedicine, 2023)
Objective: Mercuric chloride (Merc; HgCl2) is toxic to humans and animals and contributes to environmental pollution, which usually results in nerve and systemic harm to different organs. Falcaria vulgaris (FV) is a medicinal plant rich in antioxidants. This research aimed to assess the FV hydroalcoholic extract effects on kidney toxicity induced by Merc.Materials and Methods: Forty-eight male rats were divided into eight groups: the control group: received saline; the Merc group: received 0.5 ml/day of 0.5 ppm aqueous Merc; FV1, 2, and 3 groups: received 50, 100, 150 mg/kg FV, respectively; and Merc + FV1, 2, and 3 groups: received Merc and FV at three doses. The administration period was 14-days. Subsequently, kidneys and sera were cumulated from each group for the analysis. Samples were analyzed via hematoxylin-eosin staining and biochemical tests.Results: The rats that received Merc displayed significant decrement in the kidney index, the diameter of renal corpuscles, total antioxidant capacity levels, superoxide dismutase activity (all, p<0.01), and 150 mg/kg FV mitigated these outcomes (all, p<0.05). Urea, creatinine, nitric oxide, and the level of apoptosis revealed a significant increment in the kidney of the rats that received Merc (all, p<0.01), and 150 mg/kg FV decreased these results. Furthermore, FV ameliorated histological changes induced by Merc (all, p<0.05). Conclusion: The FV hydroalcoholic extract protects the kidneys against Merc-induced nephrotoxicity. Antioxidant and anti-apoptotic FV hydroalcoholic extract properties were involved in this healing effect.